Clinical Features and Multimodality Diagnostic Tools of Pulmonary Hypertension - Galuh, Lukitasari Ayu; Rahimah, Anna Fuji; Martini, Heny; Rizal, Ardian (Heart Science Journal, 2024)
Pulmonary hypertension (PH) is characterized by an increase in mean pulmonary artery pressure (mPAP) above normal, which is > 20 mmHg and an increase in pulmonary vascular resistance (pulmonary vascular resistance / PVR) above normal, in resting conditions.The pathophysiology of PH involves remodeling of the pulmonary vessels, from the main pulmonary arteries, lobar arteries, segmental arteries, distal arteries, pulmonary arterioles, capillaries to the postcapillary pulmonary veins. In general, the epidemiological figures for PH are not known with certainty. The UK reported a PH prevalence of 97 cases/1,000,000 population with a female:male ratio of 1.8. The diagnostic approach to PH is mainly focused on two things. The primary goal is to raise the initial suspicion of PH and ensure fast-track referral to a PH center in patients with a high probability of PAH, CTEPH, or other forms of severe PH. The second aim is to identify the underlying disease, particularly left heart disease (Group 2 PH) and lung disease (Group 3 PH), as well as comorbidities, to ensure appropriate classification, risk assessment, and treatment.Â The Gold Standard diagnosis and classification of pulmonary hypertension is by examining the right heart catheterization (RHC).Â Clinical scoring in the form of shortness of breath without any obvious cause accompanied by physical examination, ECG and Thorax X-ray images which depict an enlarged right heart have good sensitivity and specificity for the diagnosis of pulmonary hypertension in patients with congenital heart disease. A high right ventricular pressure, mean PAP, and BNP values during observation, as well as heart size on chest X-ray can be predictors of a poorer prognosis in this population.